16d+23=14⋅(d-2)

Combine 16 and d.

d6+23=14⋅(d-2)

Apply the distributive property.

d6+23=14d+14⋅-2

Combine 14 and d.

d6+23=d4+14⋅-2

Cancel the common factor of 2.

Factor 2 out of 4.

d6+23=d4+12(2)⋅-2

Factor 2 out of -2.

d6+23=d4+12⋅2⋅(2⋅-1)

Cancel the common factor.

d6+23=d4+12⋅2⋅(2⋅-1)

Rewrite the expression.

d6+23=d4+12⋅-1

d6+23=d4+12⋅-1

Combine 12 and -1.

d6+23=d4+-12

Move the negative in front of the fraction.

d6+23=d4-12

d6+23=d4-12

Subtract d4 from both sides of the equation.

d6+23-d4=-12

To write d6 as a fraction with a common denominator, multiply by 22.

d6⋅22-d4+23=-12

To write -d4 as a fraction with a common denominator, multiply by 33.

d6⋅22-d4⋅33+23=-12

Write each expression with a common denominator of 12, by multiplying each by an appropriate factor of 1.

Multiply d6 and 22.

d⋅26⋅2-d4⋅33+23=-12

Multiply 6 by 2.

d⋅212-d4⋅33+23=-12

Multiply d4 and 33.

d⋅212-d⋅34⋅3+23=-12

Multiply 4 by 3.

d⋅212-d⋅312+23=-12

d⋅212-d⋅312+23=-12

Combine the numerators over the common denominator.

d⋅2-d⋅312+23=-12

Simplify each term.

Simplify the numerator.

Factor d out of d⋅2-d⋅3.

Factor d out of d⋅2.

d(2)-d⋅312+23=-12

Factor d out of -d⋅3.

d(2)+d(-1⋅3)12+23=-12

Factor d out of d(2)+d(-1⋅3).

d(2-1⋅3)12+23=-12

d(2-1⋅3)12+23=-12

Multiply -1 by 3.

d(2-3)12+23=-12

Subtract 3 from 2.

d⋅-112+23=-12

d⋅-112+23=-12

Move -1 to the left of d.

-1⋅d12+23=-12

Move the negative in front of the fraction.

-d12+23=-12

-d12+23=-12

-d12+23=-12

Subtract 23 from both sides of the equation.

-d12=-12-23

To write -12 as a fraction with a common denominator, multiply by 33.

-d12=-12⋅33-23

To write -23 as a fraction with a common denominator, multiply by 22.

-d12=-12⋅33-23⋅22

Write each expression with a common denominator of 6, by multiplying each by an appropriate factor of 1.

Multiply 12 and 33.

-d12=-32⋅3-23⋅22

Multiply 2 by 3.

-d12=-36-23⋅22

Multiply 23 and 22.

-d12=-36-2⋅23⋅2

Multiply 3 by 2.

-d12=-36-2⋅26

-d12=-36-2⋅26

Combine the numerators over the common denominator.

-d12=-3-2⋅26

Simplify the numerator.

Multiply -2 by 2.

-d12=-3-46

Subtract 4 from -3.

-d12=-76

-d12=-76

Move the negative in front of the fraction.

-d12=-76

-d12=-76

Multiply both sides of the equation by -12.

-12⋅(-d12)=-12⋅(-76)

Simplify -12⋅(-d12).

Cancel the common factor of 12.

Move the leading negative in -d12 into the numerator.

-12⋅-d12=-12⋅(-76)

Factor 12 out of -12.

12(-1)⋅-d12=-12⋅(-76)

Cancel the common factor.

12⋅-1⋅-d12=-12⋅(-76)

Rewrite the expression.

-1⋅(-d)=-12⋅(-76)

-1⋅(-d)=-12⋅(-76)

Multiply.

Multiply -1 by -1.

1⋅d=-12⋅(-76)

Multiply d by 1.

d=-12⋅(-76)

d=-12⋅(-76)

d=-12⋅(-76)

Simplify -12⋅(-76).

Cancel the common factor of 6.

Move the leading negative in -76 into the numerator.

d=-12⋅-76

Factor 6 out of -12.

d=6(-2)⋅-76

Cancel the common factor.

d=6⋅-2⋅-76

Rewrite the expression.

d=-2⋅-7

d=-2⋅-7

Multiply -2 by -7.

d=14

d=14

d=14

Solve for d 1/6d+2/3=1/4*(d-2)